HNO3 partitioning in cirrus clouds - Meilinger, S. K.; Tsias, A. H.; Schiller, C.; Peter, T.; Dreiling, V.; Kuhn, M.; Feigl, C.; Schlager, H.; Curtius, J.; Sierau, B.; Arnold, F.; Zöger, M. (Geophysical Research Letters, 1999)
During the 1997 POLSTAR-1 winter campaign in northern Sweden a flight was performed across a cold trough of air (similar or equal to 196 K) in the tropopause region. Measurements of total water vapour, nitric acid, particles and reactive nitrogen (NOy) were taken. The particle measurements indicate that about 3% of the particles in the moist tropospheric air were ice particles. Forward and backward facing NOy inlets were used simultaneously to determine condensed phase HNO3. The combined NOy and particle measurements reveal that less than 1% of a monolayer of NOy could have resided on the ice particles. This casts doubt on the hypothesis that sedimenting cirrus particles generally lead to a strong downward flux of NOy. In addition to the NOy measurements, independent HNO3 measurements were used to determine total HNO3. Although quantitative uncertainties do not allow to completely rule out that the NOy uptake on ice was limited by total HNO3, the combined NOy and KNO3 data suggest that there was low uptake of NOy on ice despite abundant HNO3 in the gas phase. Model studies indicate, that the most likely explanation of the measured nitric acid partitioning is given by HNO3 in ternary solution droplets coexisting with almost HNO3 free ice in the same air mass.